Strategi Perencanaan Prasarana Sekolah dengan Enterprise Architecture dan Framework TOGAF - Paramida, Feti; Mulyana, Dadang Iskandar (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The planning and management of school infrastructure are critical for ensuring the effective delivery of educational services. This study explores the application of Enterprise Architecture (EA) using the TOGAF (The Open Group Architecture Framework) to improve the management of infrastructure at SMK IDN, an IT-focused boarding school. The research involves identifying current issues with the manual system used for infrastructure management, collecting data through observations, interviews, and document analysis, and developing a comprehensive information system that integrates and automates these processes. The TOGAF-ADM framework is employed to map the required architectural solutions, including business, application, and technology architectures. Implementation of this system aims to enhance efficiency, data consistency, and ease of asset tracking. The expected outcome is a robust, integrated information system that supports better infrastructure management, aligning with the school's mission to provide high-quality, technologically advanced education.